"We want everything in a one-stop shop": acceptability and feasibility of PrEP and buprenorphine implementation with mobile syringe services for Black people who inject drugs - Tyler S. Bartholomew; Barbara Andraka-Cristou; Rachel K. Totaram; Shana Harris; Susanne Doblecki-Lewis; Lily Ostrer; David P. Serota; David W. Forrest; Teresa A. Chueng; Edward Suarez; Hansel E. Tookes (BMC, 2022)
Abstract Introduction A recent surge in HIV outbreaks, driven by the opioid and stimulant use crises, has destabilized our progress toward targets set forth by Ending the HIV Epidemic: A Plan for America for the high-priority community of people who inject drugs (PWID), particularly Black PWID. Methods In order to ascertain the acceptability and feasibility of using a mobile syringe services program (SSP) for comprehensive HIV prevention via PrEP and medications for opioid use disorder (MOUD), our mixed methods approach included a quantitative assessment and semi-structured qualitative interviews with Black PWID (n = 30) in Miami-Dade County who were actively engaged in mobile syringe services. Results Participants felt that delivery of MOUD and PrEP at a mobile SSP would be both feasible and acceptable, helping to address transportation, cost, and stigma barriers common within traditional healthcare settings. Participants preferred staff who are compassionate and nonjudgmental and have lived experience. Conclusions A mobile harm reduction setting could be an effective venue for delivering comprehensive HIV prevention services to Black PWID, a community that experiences significant barriers to care via marginalization and racism in a fragmented healthcare system.